O impacto da educação financeira sobre a vulnerabilidade econômica em idosos de baixa renda. Uma avaliação do programa “Eu e minha aposentadoria – organizando a vida financeira” - Santos, Rafaela Aires Tavares (Universidade Federal do Tocantins, 2019)
The objective of this study was to evaluate the impact of financial education on the economic vulnerability of low income elderly people, being that the research object was the adult financial education program "I and my retirement - organizing financial life". As a trajectory of the evaluation, the program was initially structured in the north, south and central regions of the municipality of Palmas, which occurred in the period from February to April 2018, six months after the first intervention, the evaluation stage of impact. The effect of the program on the economic vulnerability of the elderly was obtained through the analysis of 5 impact indicators: 1) percentage of the monthly income of the elderly spent on basic expenses (food, health, housing); 2) saving habits; 3) financial behavior; 4) knowledge about debts and 5) default. The valuation method used was the econometric models Propensity Score Matching and Differences in Differences. The results pointed to the positive effect of the program on each of the impact indicators after the intervention. In indicator 1, the effect of the program was 17.63%; as for the indicator that analyzes savings habits, the effect was 13.8%; the effect of the program on financial behavior showed a 1.7% impact on the elderly participants; the knowledge about debt was increased by 5 percentage points and the percentage of defaulters was reduced by 9%. Overall, the results presented converge with the financial education program's proposal to reduce the economic vulnerability of the low-income elderly.